Restorative effect of insulin-like growth Factor I gene therapy in the hypothalamus of senile rats with dapaminergic neurodegeneration - Herenu, Claudia B.; Cristina, Carolina; Rimoldi, Omar J.; Becu Villalobos, Damasia; Cambiaggi, Vanina; Portiansky, Enrique L.; Goya, Rodolfo G. (Iatreia, 2005)
Insuline-like factor I (IGF-I) is emerging as a powerful reuroprotective molecule which is strongly induced in the central nervous system after different insults.